How Nurses Complement Doctors in Addressing Trauma Challenges - Sultana Mutlag Al Atawi, Badriah Abdullah Mohammed Aldusuqi, Khaled Saleh Mania Almania, Mashael Omar Yahya Almaqadi, Nasser Mashlaeh Mansor Aldosari, Muqrin Bin Saad Almansour, Zahrah Saeed Mahamed Al Qahtani, Sabah Marzoog Alharbi (Journal of International Crisis and Risk Communication Research, 2024)
Trauma is a leading cause of emergency room (ER) admissions worldwide, with road traffic accidents, falls, and violence as primary contributors. In regions such as Saudi Arabia, road traffic injuries account for the majority of trauma-related cases. This literature review explores the pivotal roles of physicians and nurses in emergency trauma care, emphasizing their distinct yet interdependent contributions. Physicians lead the assessment and management of life-threatening conditions using systematic protocols like the Advanced Trauma Life Support (ATLS) framework. Their expertise encompasses advanced diagnostics, life-saving interventions, and the implementation of emerging technologies. Conversely, nurses are instrumental in patient stabilization, continuous monitoring, and trauma-informed care, addressing both physiological and psychological needs. The review highlights interdisciplinary collaboration as the cornerstone of effective trauma care, with structured communication frameworks like SBAR improving outcomes. Furthermore, advances in technologies and evidence-based practices are reshaping roles, fostering improved survival rates and holistic patient recovery. This synthesis underscores the necessity of seamless teamwork and ongoing professional development to meet the challenges of modern trauma care.